Bubble evolution dynamics in alkaline water electrolysis - Lingao Deng; Liming Jin; Luyu Yang; Chenchen Feng; An Tao; Xianlin Jia; Zhen Geng; Cunman Zhang; Xiangzhi Cui; Jianlin Shi (eScience, 2025)
It is anticipated that alkaline water electrolysis (AWE) technology will assume a significant role in the future energy sector, facilitating the integration of renewable energy and hydrogen production. Regrettably, the efficiency of AWE is not yet optimal. In particular, the inefficiency caused by bubbles at increased current density is often overlooked, necessitating a detailed understanding of the intricate relationship between bubble evolution and electrolytic reactions. This paper presents a comprehensive review of the fundamental theory and recent research on bubbles, and outlines the primary challenges and research directions for bubble dynamics in AWE. First, the theory of bubble nucleation, growth, and detachment is reviewed and summarized. Subsequently, the impact of bubbles on the diverse processes occurring during the electrolysis reaction is meticulously delineated and examined. The following section presents a thorough compilation and categorization of the methods employed to remove bubbles, with a detailed analysis of the strategies deployed to mitigate the impact of gas bubble traffic. Additionally, an in-depth exploration of the research methodology employed at each stage of the bubble evolution process is provided. Finally, the review concludes with a summary and outlook on the opportunities and challenges associated with studying bubble dynamics in AWE, offering insights into innovative avenues for efficient electrolytic hydrogen production.